Central muscle relaxants in rheumatology practice - E. Yu. Polishchuk; A. S. Potapova; A. E. Karateev (Современная ревматология)
The article describes the general principles of the treatment of musculoskeletal pain, discusses modern approaches to the treatment of osteoarthritis (OA) and nonspecific back pain (NBS). The issues discussed are: the efficacy and tolerability of the combined use of non-steroidal anti-inflammatory drugs (NSAIDs) of predominantly selective action (aceclofenac) and a centrally acting muscle relaxant (tolperisone) in the treatment of OA and NBS. Two clinical observations are presented that confirm the benefits of combined administration of NSAIDs and muscle relaxants in the treatment of OA and NBS. The efficacy and favorable safety profile of aceclofenac has been demonstrated in patients with comorbid diseases. Tolperisone has shown its efficacy both as a mean of controlling pain associated with muscle tension, and as an element of combination therapy not only for NBS, but also for OA.